Effects of calcitonin and calcium medication in treatment of edentulous osteoporotic mandible - Poštić Srđan D. (Vojnosanitetski Pregled)
Background/Aim. In addition to damage of the bones that support the remaining teeth, degradation of osteoporotic oral bones also lead to a consequent reduction of supporting tissues and the loss of dentures retention. The aim of this study was to assess the clinical and radiographic outcomes following injection of a calcitonin and calcium solution into the buccal aspects of edentulous mandibles. Methods. The experimental group of 67 edentulous patients diagnosed with osteoporosis, and the control group of 19 nonosteoporotic edentulous patients were treated with the calcitonin and calcium once solution per month. Mandibular bone density was measured from panoramic radiographs, supplemented by T scores of skeletal density in the experimental group. Results. After the therapy, measurements showed moderate increases in bone density, compensating for up to 4% of the total loss of minerals and solidity of denture-bearing areas of osteoporotic mandibles. Osteoporosis affected women earlier than men in this study. Conclusion. Application of a calcitonin and calcium solution is a suitable method of preprosthetic therapy for edentulous osteoporotic patients.